Theory of the Solution of Inventive Problems for Flexure Design in Micro-Electro-Mechanical Systems - Huiling Yu; Shanshan Cui (Institute of Advanced Engineering and Science, 2014)
In this paper detail of the optimization of a flexure design which is used in many MEMS devices will be presented. Due to a difference in thermal expansion coefficients between the flip-chip bonded MEMS device and the substrate, cooling after bonding can cause the MEMS to buckle; It is necessary to decrease the influence of distortion by using the correct material selection, welding method, weld design, fixture design, temperature control and TRIZ. We can seek out principles that can solve the problem. It can be concluded that an optimal flexure design will include the longest fold length and smallest fold spacing possible. By solving the deformation problem of MEMS devices can promote the development of flip chip technology, and make for the further application of the TRIZ theory in the study of forestry equipment.